2015
DOI: 10.1007/s10640-015-9921-1
|View full text |Cite
|
Sign up to set email alerts
|

National Accounting and the Valuation of Ecosystem Assets and Their Services

Abstract: There has long been interest in integrating the value of environmental stocks and flows into standard measures of economic activity and wealth, in particular through the development of adjusted measures of GDP and extended measures of national wealth. This paper examines how the valuation of ecosystem services and ecosystem assets can be undertaken in an integrated national accounting setting. We clarify the relevant valuation principles, most significantly the need to apply the concept of exchange values, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(84 citation statements)
references
References 35 publications
0
84
0
Order By: Relevance
“…It is potentially aligned with a natural capital accounting approach to valuation (Obst et al, 2016), see the 'Discussion' section. It also has the potential advantage that both high and low outliers do not significantly affect VOLY, and that there is no need for arbitrary selection of outliers on either the lower or the higher boundary of the range of WTP estimates.…”
Section: The Msr Approach To Measure Volymentioning
confidence: 99%
See 2 more Smart Citations
“…It is potentially aligned with a natural capital accounting approach to valuation (Obst et al, 2016), see the 'Discussion' section. It also has the potential advantage that both high and low outliers do not significantly affect VOLY, and that there is no need for arbitrary selection of outliers on either the lower or the higher boundary of the range of WTP estimates.…”
Section: The Msr Approach To Measure Volymentioning
confidence: 99%
“…These studies shown a very wide range for VOLY, varying from several thousand euros to well over 100,000 EUR (see, for example, Chilton et al, 2004;Desaigues et al, 2011;Chanel and Luchini, 2014). In addition, there is increasing interest in natural capital accounting, which requires a different approach to monetary valuation compared to CBA (Obst et al, 2016). In natural capital accounting, valuation methods for environmental assets such as clean air are still under development (UN et al, 2014;Obst et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second report further notes that the use of economic valuation of ecosystem (Luisetti et al 2013, Costanza et al 2014. Obst et al (2015) argue that the issues related to the valuation of ecosystem services and their relationship with ecosystem assets for their consideration for national accounting purposes need to be better articulated because several conceptual and measurement challenges still have to be resolved.…”
Section: Recommendation 5: Provide Guidelines For the Use And Interprmentioning
confidence: 99%
“…For ecosystem services provision at the practical policy level, however, the decision on whether the 'next unit' is meaningful in terms of marginal analysis is conditioned by the scale (local, regional or global) of the policy decision (Fisher et al 2008) as the consequences of the 'marginal' change may acquire a completely different perspective and meaning at different scales. Furthermore, within the national green accounting context, Obst et al (2015) services for the integration of the ecosystems and their services within national accounts is complex and still under development. 4 The issues surrounding the use of environmental valuation have been discussed in detail elsewhere (e.g.…”
Section: Recommendation 5: Provide Guidelines For the Use And Interprmentioning
confidence: 99%